Judicializing Foreign Affairs: The Canada-Saudi Arms Deal and the Implications of Transnational Tort Litigation - Ahmad, Hassan M. (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2020)
In the recent past, the ability to challenge Canadian government action with foreign relations elements has spilled over from administrative law into tort law. At the same time, tort actions against multinational corporations for human rights violations abroad have also seen a surge in Canadian courts, culminating in the Supreme Court’s recent decision in Nevsun Resources Ltd. v. Araya. This article addresses some doctrinal elements of a potential transnational tort claim against the Canadian government and a Canadian arms manufacturer pursuant to human rights violations arising from the 2014 Canada-Saudi Arms Deal [CSAD]. It also explores consequential effects that Canada’s burgeoning transnational tort laws can have on Canada-Saudi relations as well as the Canadian defence industry. Overall, this article uses the CSAD as one real-life scenario in which private law litigation can have broader effects on a country’s foreign relations and domestic economy. In this instance, the judiciary’s power to exact extra-judicial consequences illustrates how tort litigation can curtail the behaviour of governmental and commercial actors.